The contribution of graduate research to inclusive education: a diagnosis of multifunctional resource rooms in basic education in União da Vitória, PR - Ferreira, Lislaine Paula Queiróz; Silva, Madalena Pereira da (Debates em Educação, 2024)
This article, based on research conducted within the Professional Master’s Program in Basic Education, aims to discuss the connections between graduate research and Basic Education, focusing on a diagnostic of accessibility conditions in Multifunctional Resource Rooms (MRRs). Given the essential role of schools in ensuring accessible and inclusive environments for Special Education students, this study aimed to investigate whether the MRRs in the schools of União da Vitória, PR, adhere to accessibility principles. The research follows a qualitative approach and was conducted in two schools within the Municipal Education Network, with data collected through questionnaires and analyzed using content analysis. The results indicated that the schools have both unique and common aspects across different dimensions of accessibility, reflecting the diversity of the student profiles served. Collaboration among family, school, and society was also valued in the development of students as citizens. Regarding the six dimensions of accessibility analyzed, neither school fully meets the criteria across all dimensions, highlighting weaknesses and the need for greater attention to accessibility in MRRs. These findings emphasize the importance of applied graduate research as a tool to enhance inclusive practices in Basic Education.